Modeling the Impact of Vector Reduction and Natural Recovery on the Transmission Dynamics of Malaria - K, Adamu A.; O, Ajor E.; A, Olopade I.; M, Bulus S.; W, Barde; D, Yavalah (Darul Yasin Al Sys, 2025)
A mathematical modeling of the impact of vector reduction and natural recovery on the transmission dynamics of malaria was carried out. We present a deterministic model for the transmission dynamics of malaria in which natural recovery and vector reduction were both important for the disease management. We estimated the basic reproduction number using the next generation matrix method and investigated the local stability of the disease free equilibrium points of the model. Sensitivity analysis and Numerical simulations of the basic reproduction number with respect to the model parameters were carried out. Our result shows that effective vector reduction and increased natural recovery will reduce the spread of malaria.